(untitled) (Bangladesh Journal of Medical Education, 2021)
This study aimed to evaluate the trend of production (2007-2016) and associated factors of seven health professionals i.e. physicians, dentists, diploma nurses, bachelor nurses, midwives, medical assistants and medical technologists in Bangladesh. The study team adopted a mapping approach to geographically locate all the health professional education institutions recognized by the Ministry of Health and Family Welfare (MOHFW). This was supported by a mixed-method design combining qualitative (e.g. group discussions and key informant interviews) and quantitative (questionnaire survey) methods. From 2007 to 2016, a total of 107,406 students graduated from all seven professional categories. Out of the total, about 40% belonged to the MBBS physician, 6% dentists, 15% medical assistants, 18% medical technologists, 21% nurses, and only 1% to the midwives. So, a skill-mix imbalance exists at the production level. Though the production had been on rising last 10 years, the production of the physicians was higher than any other professional categories. Feminization of the workforce is prominent as there was an average 14% increase of the female doctors than the male. The increasing production of health professionals needs to be supported by proper planning and policy interventions in order to avoid distortion of skill mix. Growing feminization of the workforce is also another area that requires special attention on the development of gender-sensitive employment conditions. Bangladesh Journal of Medical Education Vol.12(2) July 2021: 30-46